Coffin-Siris syndrome with Mayer-Rokitansky-Küster-Hauser syndrome: a case report - Shukla Umesh (Journal of Medical Case Reports, 2010)
Abstract Introduction We report the case of an unusual association of Coffin-Siris syndrome with Mayer-Rokitansky-Küster-Hauser syndrome. This association has never previously been reported in the medical literature. Case presentation A nine-year-old Indian girl was referred to our hospital for growth retardation, mental retardation, lax joints, generalized hypertrichosis, and hypoplastic fifth fingernails and toenails. A thorough medical examination and evaluation revealed she had phenotypic features of Coffin-Siris syndrome, with Mayer-Rokitansky-Küster-Hauser syndrome on radiological evaluation. The karyotype of our patient was normal. Conclusion In an unexplained case of mental retardation with facies suggestive of Coffin-Siris syndrome, association with Mayer-Rokitansky-Küster-Hauser syndrome should be considered and the patient should be evaluated for the same. Both of these syndromes may have a common pathogenesis, as yet unknown. This case report has broad implications, as similar cases in future may give insights into the pathogenesis of both these syndromes.